2006
DOI: 10.1016/j.neulet.2005.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Visual cortex activation in late-onset, Braille naive blind individuals: An fMRI study during semantic and phonological tasks with heard words

Abstract: Visual cortex activity in the blind has been shown in Braille literate people, which raise the question of whether Braille literacy influences cross-modal reorganization. We used fMRI to examine visual cortex activation during semantic and phonological tasks with auditory presentation of words in two late-onset blind individuals who lacked Braille literacy. Multiple visual cortical regions were activated in the Braille naive individuals. Positive BOLD responses were noted in lower tier visuotopic (e.g., V1, V2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…Consistent with this finding is the observation that the posterior auditory field, also known for its involvement in auditory localization behaviors (18), is necessary for enhanced visual localization abilities in congenitally deaf cats (11). Furthermore, in early-blind individuals, lexigraphical regions of visual cortex are activated by Braille reading (19) and the nonvisual spatial properties of medial occipital cortex are retained (29). Thus, for a given cortical region, functional specificity is preserved following deafness/blindness despite substitutions among the input modalities.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Consistent with this finding is the observation that the posterior auditory field, also known for its involvement in auditory localization behaviors (18), is necessary for enhanced visual localization abilities in congenitally deaf cats (11). Furthermore, in early-blind individuals, lexigraphical regions of visual cortex are activated by Braille reading (19) and the nonvisual spatial properties of medial occipital cortex are retained (29). Thus, for a given cortical region, functional specificity is preserved following deafness/blindness despite substitutions among the input modalities.…”
Section: Discussionmentioning
confidence: 58%
“…One clue might be the observation that the posterior auditory field of hearing animals is involved in auditory localization (18) whereas the same region in congenitally deaf animals underlies their improvement in visual localization of peripheral targets (11). Similarly, following early blindness, the lexigraphic components of Braille reading provide activation of visual cortex (19). Therefore, it seems possible that the behavioral role of a crossmodally reorganized area is related to its role in hearing/sighted individuals.…”
mentioning
confidence: 99%
“…These results suggest that vibrotactile inputs probably activate the visual cortex through some latent pathway common to both blind and sighted subjects [21]. Burton et al [22] also suggested that the learning effect may be important in the V1 activation in the blind. Using fMRI in late-onset but Braille naĂŻve blind individuals, and auditory-presented phonological tasks, they found task-related activation in both lower tier and higher tier visual areas.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, cross-modal reorganization of the lower tier visual areas, which are not cross-modally responsive in sighted people, may be recruited particularly through regularly attending to selected non-visual inputs. Such learning might be needed to strengthen the more remote connections with multisensory cortical areas [22]. Cross-modal reorganization of lower tier visual areas may thus be triggered in sighted subjects by learning skills such as Mah-Jong discrimination.…”
Section: Resultsmentioning
confidence: 99%
“…In blind but not sighted people, language tasks activate regions in occipital and temporal cortex that correspond to visually activated areas in sighted (Kujala et al 1995a; Sadato et al 1996; BĂŒchel et al 1998a, 1998b; Melzer et al 2001; Burton et al 2002a, 2002b, 2003, 2006; Röder et al 2002; Amedi et al 2003; Burton 2003; Burton and McLaren 2006). The functional reorganization of these regions in the blind possibly aids in semantic word generation and word memory retrieval (Amedi et al 2003).…”
Section: Introductionmentioning
confidence: 99%